Mfsd2a suppresses colorectal cancer progression and liver metastasis via the S100A14/STAT3 axis - Linfeng Sun; Xiangdong Li; Yuhao Xiao; Wenjie Yu; Xuyang Chen; Ziyi Wang; Nan Xia; Xuejiao Chen; Minhao Chen; Haoliang Zhu; Jie Li; Jie Wei; et al. (Journal of Translational Medicine)
Abstract Background Colorectal cancer (CRC) exhibits a high incidence globally, with the liver being the most common site of distant metastasis. At the time of diagnosis, 20–30% of CRC patients already present with liver metastases. Colorectal liver metastasis (CRLM) is a major cause of mortality among CRC patients. The pathogenesis of CRLM involves complex molecular mechanisms and the hepatic immune microenvironment, but current clinical prevention and treatment are significantly limited. Recent studies have revealed that the major facilitator superfamily domain containing protein-2a (Mfsd2a) plays a pivotal role in the development and metastasis of various cancers. For instance, Mfsd2a inhibits gastric cancer initiation and progression and may impact angiogenesis. However, the mechanisms by which Mfsd2a influences CRC progression and liver metastasis remain unclear. Methods In this study, we conducted a survival analysis of Mfsd2a in colorectal cancer using data from the GEPIA and GEO databases, and examined the expression differences between primary tumor (PT) and liver metastasis (LM). We further assessed the clinical significance and prognostic relevance of Mfsd2a through immunohistochemical analysis of tissue samples from 70 CRLM patients. Moreover, Kaplan-Meier analysis was used to perform survival analysis on these patients. The biological function of Mfsd2a in CRLM was confirmed by a series of experiments conducted both in vitro and in vivo. Additionally, we investigated downstream molecular pathways using western blot, Co-immunoprecipitation, immunofluorescence, and mass spectrometry techniques. Results We observed that Mfsd2a expression is reduced in LM compared to PT, and higher Mfsd2a levels are associated with better prognosis in CRLM patients. Furthermore, function assays demonstrated that Mfsd2a suppresses CRC cells proliferation, migration, invasion, and EMT in vitro, while also delaying tumor growth and liver metastasis in vivo. Mechanistically, Mfsd2a interacts with S100A14, enhancing its expression and inhibiting phosphorylation of STAT3. In addition, the STAT3 activator colivelin partially reversed the inhibitory effect of Mfsd2a overexpression on the progression of colorectal cancer and liver metastasis. Conclusion In summary, Mfsd2a inhibits colorectal cancer progression and liver metastasis by interacting with S100A14, thereby suppressing the phosphorylation of STAT3. Mfsd2a functions as a tumor suppressor in CRLM and could be a promising therapeutic target for treating CRC patients with liver metastasis. Graphical abstract